PENDEKATAN METODOLOGIK MATEMATIKA DALAM EKONOMI DAN BISNIS ISLAM - Latifah, Eny; Abdullah, Rudi (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2023)
The purpose of this research is to find out what approaches exist in mathematics in Islamic economics and business. The research method used is literature by collecting sources from literacy: journals, articles, books and other written works to get the information needed. The results of the study show that mathematics uses a methodological approach: (1) Inductive-Deductive (presentation of material from specific-general examples and vice versa, then it is required to draw conclusions); (2) Informal-Formal; (3) Intuitive-Axiomatic (Intuitive: Thinking instinctively on understanding the mathematical concepts of Islamic economics and business, Axiomatic: understanding concepts by using rules); (4) Analytical-Synthetic (Analytic: how to do mathematics starting from things that are known, Synthetic: Explaining the things that are questionable); (5) Problem Sloving-Posing: using non-routine logarithms in solving, conceptualizing and assuming something to find a solution). (6) Thematic-Realistic; (7) Open-Ended; (8) Constructivism; (9) Spiral; (10) Active Student Learning Methods; and (11) Process Skills.